2017
DOI: 10.1186/s12889-017-4517-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced egfr, elevated urine protein and low level of personal protective equipment compliance among artisanal small scale gold miners at Bibiani-Ghana: a cross-sectional study

Abstract: BackgroundMercury is a toxic metal with its effects on human health ranging from acute to chronic in a very short time of exposure. Artisanal and small-scale gold mining (ASGM) is the main source of direct human exposure to mercury.AimTo access the effect of mercury exposure on the renal function and level of personal protective equipment (PPE) compliance among small-scale gold miners in Bibiani District of the Western Region of GhanaMethod110 consenting male gold miners were purposively recruited for this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…Occupational mercury exposure levels have been linked to several factors including the number of years of exposure, type and nature of mercury and state of mercury [ 22 ]. In line with our current data, previous studies conducted in South Africa [ 23 ], Venezuela [ 24 ] and Ghana [ 14 , 25 ] have demonstrated that a high percentage of small scale miners are exposed to mercury above the occupational threshold. Mercury toxicity is characteristically insidious [ 26 ] which supports our finding that extended work duration is associated with increased blood mercury level among small-scale miners.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Occupational mercury exposure levels have been linked to several factors including the number of years of exposure, type and nature of mercury and state of mercury [ 22 ]. In line with our current data, previous studies conducted in South Africa [ 23 ], Venezuela [ 24 ] and Ghana [ 14 , 25 ] have demonstrated that a high percentage of small scale miners are exposed to mercury above the occupational threshold. Mercury toxicity is characteristically insidious [ 26 ] which supports our finding that extended work duration is associated with increased blood mercury level among small-scale miners.…”
Section: Discussionsupporting
confidence: 92%
“…The method for blood mercury analysis was similar to the procedure reported in our earlier study [ 14 ]. Wet digestion of blood mercury was performed at research the laboratory in the School of Agricultural of the University of Cape Coast.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were studies on the neurotoxicity of mercury (Sheehan et al 2014;Bose-O'Reilly et al 2012), other forms of biomonitoring studies (Sanders et al 2014) and mercury level measurements in the environment (Gonzalez-Merizalde 2016). There were still those who focus their studies on the mercury levels on human hair (Langeland et al 2017) and urine and blood samples (Afrifa et al 2017).…”
Section: Gap Analysis On Health and Environmental Methodologies In Asmmentioning
confidence: 99%